Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa pada Mata Pelajaran PPKn Kelas VII di SMP Negeri 1 Pariaman - Fadhilaturrahmy, Fadhilaturrahmy; Bentri, Alwen; Rayendra , Rayendra; Masnur, Alkadri (Indo-MathEdu Intellectuals Journal, 2024)
The problem found in the learning process taking place in the field is that students are found who cannot cooperate by upholding group norms in achieving their learning goals. This affects the understanding and learning outcomes of students. This study aims to determine the influence of the application of the Jigsaw-type cooperative learning model on student learning outcomes in PPKn grade VII subjects of SMP Negeri 1 Pariaman. This type of research is quasy-experimental research consisting of 2 classes, namely the experimental class and the control class. The sample technique used in this study is purposivesampling. This research was conducted on the material of Indonesian Unity and Regional Characteristics in the subject of PPKn class VII. The instrument used is a test of students' understanding of the subject matter. The analysis test uses the t-test. The results of the study showed that the data analyzed using the t-test had a significant level of 0.05. namely the results of the thitun > ttable, which are 1.823 > 0.670. Based on the results of the study, it can be concluded that H1 in this study is accepted. Thus, the application of the Jigsaw-type cooperative learning model has an effect on student learning outcomes in PPKn class VII SMP Negeri 1 Pariaman.